2013
DOI: 10.1007/s11103-013-0122-4
|View full text |Cite
|
Sign up to set email alerts
|

Inducible expression of p50 from TMV for increased resistance to bacterial crown gall disease in tobacco

Abstract: The dominant tobacco mosaic virus (TMV) resistance gene N induces a hypersensitive response upon TMV infection and protects tobacco against systemic spread of the virus. It has been proposed to change disease resistance specificity by reprogramming the expression of resistance genes or their corresponding avirulence genes. To reprogramme the resistance response of N towards bacterial pathogens, the helicase domain (p50) of the TMV replicase, the avirulence gene of N, was linked to synthetic promoters 4D and 2S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Plants are often exposed to many various bacterial, viral, and fungal pathogens but have evolved potent defense systems to protect themselves [7]. In defense responses of plants, the identification of microbial pathogens plays a key role, as it "turns on" the signal transduction pathway which activates the expression of numerous pathogenresponsive genes [8,9]. These disease resistance genes are crucial for identifying the effector proteins during the process of pathogen infection [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants are often exposed to many various bacterial, viral, and fungal pathogens but have evolved potent defense systems to protect themselves [7]. In defense responses of plants, the identification of microbial pathogens plays a key role, as it "turns on" the signal transduction pathway which activates the expression of numerous pathogenresponsive genes [8,9]. These disease resistance genes are crucial for identifying the effector proteins during the process of pathogen infection [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to obtain plants that are resistant to crown gall disease, much research has been devoted to producing sense and antisense strands of the oncogene sequence by placing these sequences between opposing strong constitutive promoters [13], or to silencing the involved bacterial oncogenes by using premature stop codons [14]. The study of Niemeyer et al (2014) demonstrated a successful reprogramming of the viral N gene response against crown gall disease [9]. In recent years, Rosalia Deeken's group has been working on the molecular mechanism between crown gall disease and A. tumefaciens in Arabidopsis thaliana [8,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, avirulence genes can be linked with pathogen-responsive promoters to reprogramme corresponding resistance genes to the specificity of the promoter. Recently, the TMV resistance gene N was reprogrammed to protect tobacco against Agrobacterium-mediated crown gall disease (Niemeyer et al, 2014). In this system, unspecific expression of the avirulence gene also led to background necrosis and to spreading necrosis after Agrobacterium infection.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two efficient synthetic promoters (4D and 2S2D) were constructed by coupling either the D or the D/S elements from parsley plants to the CaMV 35S core promoter (Niemeyer et al 2014). Both promoters were fused to the helicase domain (p50) of TMV replicase and cloned into a T-DNA vector.…”
Section: Biotic Stress-inducible Synthetic Promotersmentioning
confidence: 99%